Diagnosed behavioral health conditions during the perinatal period among a commercially insured population by race/ethnicity, 2008-2020 - Dana C. Beck; Karen Tabb; Anca Tilea; Ashlee J. Vance; Stephanie Hall; Amy Schroeder; Kara Zivin; Kara Zivin; Kara Zivin (Frontiers Media S.A., 2024)
ObjectiveWe sought to examine trends in diagnosed behavioral health (BH) conditions [mental health (MH) disorders or substance use disorders (SUD)] among pregnant and postpartum individuals between 2008-2020. We then explored the relationship between BH conditions and race/ethnicity, acknowledging race/ethnicity as a social construct that influences health disparities.MethodsThis study included delivering individuals, aged 15-44 years, and continuously enrolled in a single commercial health insurance plan for 1 year before and 1 year following delivery between 2008-2020. We used BH conditions as our outcome based on relevant ICD 9/10 codes documented during pregnancy or the postpartum year.ResultsIn adjusted analyses, white individuals experienced the highest rates of BH conditions, followed by Black, Hispanic, and Asian individuals, respectively. Asian individuals had the largest increase in BH rates, increasing 292%. White individuals had the smallest increase of 192%. The trend remained unchanged even after adjusting for age and Bateman comorbidity score, the trend remained unchanged.ConclusionsThe prevalence of diagnosed BH conditions among individuals in the perinatal and postpartum periods increased over time. As national efforts continue to work toward improving perinatal BH, solutions must incorporate the needs of diverse populations to avert preventable morbidity and mortality.